Deprivation, class and crisis in Europe: a comparative analysis. Issue 2 (15th March 2019) - Grasso, Maria; Karampampas, Sotirios; Temple, Luke; Yoxon, Barbara
ABSTRACT: Analysing data from an original cross-national survey conducted in 2015 in nine European democracies covering five different types of welfare regime and asking individuals a variety of questions on their deprivation during the crisis, this paper shows that there are important cross-national and cross-class inequalities in deprivation as reported by individuals in different social classes. Cross-nationally, deprivation patterns reflected the welfare regimes of the nine countries as well as the severity of the economic crisis. Working class individuals in countries that were not so deeply affected by the crisis were generally found to be worse off than middle class individuals in countries that were more deeply affected. Semi/unskilled manual classes were found to be the most deprived and class differentials were diminished but not accounted for in multilevel models including a series of controls linked to risk factors and socio-demographic position. At the macro-level, higher inequality as measured by the Gini coefficient was associated with higher levels of reported deprivation. However, cross-level interaction tests did not provide evidence that being in semi/unskilled manual occupations has a further heightened effect on reported deprivation in contexts of higher inequality or lower social spending.